2021
DOI: 10.1038/s41467-020-20628-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon hollow fiber membranes for a molecular sieve with precise-cutoff ultramicropores for superior hydrogen separation

Abstract: Carbon molecular sieve (CMS) membranes with rigid and uniform pore structures are ideal candidates for high temperature- and pressure-demanded separations, such as hydrogen purification from the steam methane reforming process. Here, we report a facile and scalable method for the fabrication of cellulose-based asymmetric carbon hollow fiber membranes (CHFMs) with ultramicropores of 3–4 Å for superior H2 separation. The membrane fabrication process does not require complex pretreatments to avoid pore collapse b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(92 citation statements)
references
References 50 publications
2
68
1
Order By: Relevance
“…The hardness and Young's modulus obtained from loaddisplacement curves of nanoindentation tests show that the HCMS membranes possess substantially improved mechanical properties compared to the CMS membranes prepared at the same pyrolysis temperature (Figure 1f and Figure S5, Supporting Information). [33] The results verify the good compatibility between the two carbonized phases in the HCMS membranes, ensuring their practical use with excellent mechanical robustness.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The hardness and Young's modulus obtained from loaddisplacement curves of nanoindentation tests show that the HCMS membranes possess substantially improved mechanical properties compared to the CMS membranes prepared at the same pyrolysis temperature (Figure 1f and Figure S5, Supporting Information). [33] The results verify the good compatibility between the two carbonized phases in the HCMS membranes, ensuring their practical use with excellent mechanical robustness.…”
Section: Resultssupporting
confidence: 56%
“…Above 550 °C, the weight loss becomes less pronounced, and further temperature increases typically induce a more ordered carbonaceous structure in the resulting CMS and HCMS membranes. [7,32,33] In this study, CMS membranes from the pure 6FDA-DAM precursor are denoted as CMS-OOO, while those from the UiO-66-NH 2 (20 wt%)/6FDA-DAM MMM precursor are shown as HCMS-OOO, and pyrolyzed UiO-66-NH 2 nanoparticles are named UiO-OOO. Here, OOO indicates the pyrolysis temperature at the isotherm stage (550, 700, and 800 °C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lei et al reported the fabrication of cellulose-based porous carbon hollow fibers. 127 By tuning the coagulation temperature of the microcrystalline cellulose/ionic liquid/water system, the obtained carbon fibers exhibited an asymmetric structural morphology throughout their body, including a porous inner layer, a middle layer rich in macrovoids and a dense outer layer. By controlling the conversion of sp 3 to sp 2 hybridized carbon via different the carbonisation temperature, finely tuned ultramicropores were achieved in the dense outer layer of the PCF (Fig.…”
Section: Fabrication Of Pcfs With Different Porous Structuresmentioning
confidence: 99%
“…Undoubtedly, faced with the threats of depletion of petrochemical resource, catastrophic extreme weather, and burgeoning energy demand, all countries are driven to seek for renewable resources for sustainable development [1]. Among a variety of sustainable resources known to date, hydrogen is a compelling one, because of its high heating value and zero-carbon emission.…”
Section: Introductionmentioning
confidence: 99%